PreAdolescent CardioMetabolic Associations and Correlates : PACMAC : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in School of Sport and Exercise at Massey University, Wellington, New Zealand - Castro, Nicholas (Massey University, 2018)
Cardiovascular disease is typically associated with adults; however, atherosclerosis often initiates during preadolescence and has been linked to cardiometabolic risk factors. Preceding cardiometabolic risk factors include lifestyle factors: body fatness, physical fitness, physical [in]activity, sedentary behaviour, nutrition, and sleep. No known study has comprehensively assessed simultaneous associations among lifestyle factors with cardiometabolic risk factors in preadolescent children. A multicentred cross-sectional study design was utilised to investigate lifestyle factor associations with cardiometabolic risk factors in a sample of 392 children aged 8 to 10 years. Participants were recruited from primary schools located in the Wellington, Canterbury, and Otago regions in New Zealand. Data collection was carried out over 5 days between 09:00 a.m. and 12:00 p.m. at each location. The first objective assessed the associations among physical fitness, physical [in]activity, sedentary behaviour, nutrition, and sleep with body fatness indicators (body fat percentage, fat mass index, body mass index, and waist-to-hip ratio). Results indicated nutrition independently associated with body fat percentage (𝘱 < 0.05), whereas cardiorespiratory fitness significantly associated with all four body fatness indicators (𝘱 < 0.05). The second objective assessed the associations among body fatness, physical fitness, physical [in]activity, sedentary behaviour, nutrition, and sleep with cardiometabolic factors (blood pressure, cholesterol, vascular, and carbohydrate-metabolic). Results indicated body fat percentage associated with the blood pressure factor (𝘱 < 0.05); sedentary minutes, social jetlag, and Fruit and Vegetables pattern associated with the cholesterol factor (all 𝘱 < 0.05); sedentary minutes and Processed Food pattern associated with the vascular factor (both 𝘱 < 0.05); and cardiovascular fitness (V̇O₂max) and handgrip strength associated with the carbohydrate-metabolic factor (both 𝘱 < 0.001). Accordingly, body fatness, physical fitness, nutrition, and sleep all associated with at least one cardiometabolic factor. Cardiorespiratory fitness associated with cardiometabolic health and was the key finding in Objective 1; therefore, physical fitness may be the most important lifestyle factor. However, as nutrition, sleep, sedentary behaviour, and body fatness also associated with cardiometabolic health, it appears one specific lifestyle factor does not entirely explain cardiometabolic health in preadolescent children, and thus a multimodal approach for health is required for this population.
Keywords: Cardiovascular system; Diseases; Risk factors; Children; Health and hygiene; New Zealand; 420702 Exercise physiology